WOMEN AND LEADERSHIP IN CANADIAN EDUCATION (Editors: Cecilia Reynolds & Beth Young) - Sinacore-Guinn, Ada L. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1996)
CECILIA REYNOLDS & BETH YOUNG (EDITORS). Women and Leadership in Canadian Education. Calgary: Detselig Enterprises, 1995. 253 pp. $26.95. ISBN 1-55050-116-9.